Serum and Tear Leptin Levels in Patients with Allergic Conjunctivitis - Turgut, Burak; Kurt, Juelide; Ilhan, Nevin; Koca, Suleyman Serdar; Demir, Tamer; Celiker, Uelkue (Ortadogu Ad Pres & Publ Co, 2010)
Objective: The production of leptin that acts as a pro-inflammatory mediator is increased in patients with various inflammatory and allergic diseases. Our aim was to investigate the serum and tear leptin levels in patients with perennial allergic conjunctivitis and to compare them with healthy controls. Material and Methods: Fifteen patients with perennial allergic conjunctivitis (8 females and 7 males, mean age: 22 years, mean body mass index: 24.17 +/- 5.64 (+/- SD) kg/m(2)) were included in the study. Gender, body mass index and age-matched 15 healthy subjects (8 females, 7 males, mean age: 25, mean BMI: 22.47 +/- 3.56 kg/m(2)) were selected as the control group. Serum and tear leptin levels were measured with enzyme-linked immunosorbent assay (ELISA) method. Results: Serum leptin levels showed no significant difference between the patients and controls (9.79 +/- 7.73 n g/ml vs. 10.49 +/- 7.26 n g/ml, p> 0.05). Tear leptin levels showed no significant difference between the patients and controls (8.90 +/- 1.81 pg/ml vs. 8.68 +/- 1.70 pg/ml, p> 0.05). Conclusion: Our data suggest that serum and tear leptin levels do not change in patients with perennial allergic conjunctivitis. Further studies are needed to investigate the levels of free and bound leptin and to determine leptin's role in the pathogenesis of perennial allergic conjunctivitis.
Allerjik konjonktivitli hastalarda serum ve gözyasi leptin düzeyleri
Keywords: Leptin; conjunctivitis, allergic; inflammation